Effectiveness of chemical protection of chickpea crops depending on the effect of different herbicides and seed rates - Y. Makuch; S. Moshkivska; V. Smih (Карантин і захист рослин)
Goal. Search and evaluate the effectiveness of herbicides and their compositions in chickpea crops. On the basis of research to prepare a comprehensive system of protection of chickpea crops from the presence of weeds, which ensures high yields and is economically and environmentally feasible in the conditions of the Right-bank Forest-Steppe of Ukraine.